Inhibition of TEM-2 beta-lactamase from Escherichia coli by clavulanic acid: observation of intermediates by electrospray ionization mass spectrometry. - Brown, R; Aplin, RT; Schofield, C (1996)
Clavulanic acid, the therapeutically important inhibitor of beta-lactamases containing a nucleophilic serine residue at their active sites, inhibits Escherichia coli TEM-2 beta-lactamase via a complex mechanism. Electrospray ionization mass spectrometry (ESIMS) studies revealed that a minimum of four different modified proteins are formed upon incubation of clavulanate with the TEM-2 enzyme. These exhibit mass increments relative to the unmodified TEM-2 beta-lactamase of 52, 70, 88, and 155 Da. Time course studies implied that no long-lived forms of clavulanate-inhibited TEM-2 beta-lactamase retain the carbons of the oxazolidine ring of clavulanate. The absence of a 199 Da increment to unmodified TEM-2 suggests rapid decarboxylation of clavulanate upon binding to the enzyme. Proteolytic digestions of purified forms of clavulanate inhibited TEM-2 beta-lactamase followed by analyses using high-performance liquid chromatography coupled to ESIMS (HPLC-ESIMS) and chemical sequencing were used to provide positional information on the modifications to the enzyme. Increments of 70 and 80 Da increments were shown to be located in a peptide containing Ser-70. A further 70 Da mass increment, assigned as a beta-linked acrylate, was localized to a peptide containing Ser-130. A mechanistic scheme for the reaction of clavulanate with TEM-2 beta-lactamase is proposed in which acylation at Ser-70 and subsequent decarboxylation is followed either by cross-linking with Ser-130 to form a vinyl ether or by reformation of unmodified enzyme via a Ser-70 linked (hydrated) aldehyde. Purified cross-linked vinyl ether was observed to slowly convert under acidic conditions to a Ser-70 linked (hydrated) aldehyde with concomitant conversion of Ser-130 to a dehydroalanyl residue.